PENYULUHAN BAHAYA BTP PEWARNA PADA ANAK ANAK DI UPT SPF SDN KOMPLEKS IKIP - Nuramaniyah Taufiq; Andis Sugrani (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
School children do not understand how to choose healthy snacks so that it is bad for their own health. Children buy snacks according to their preferences without thinking about the ingredients contained in them. School children usually have more activities outside the home and often forget mealtimes so they buy snacks at school to block their stomachs, synthetic dyes which have advantages such as being more stable, resistant to various environmental conditions, the coloring power is stronger and has a wider color range and is easy to use. The first stage: conduct questions and answers to students about whether they know about coloring substances in food Second stage: educate students UPT SPF SDN KOMPLEKS IKIP about coloring substances in food The second stage: measuring students' knowledge of UPT SPF SDN IKIP KOMPLEKS students about coloring substances in food after counseling. There has been an increase in students' knowledge of coloring substances in food and beverages with the posttest results. Awareness of chemicals, especially dyes in food and beverages still needs to be increased. This counseling activity needs to be accompanied by training to identify dyes so that students can increase their knowledge of dyes